2018
DOI: 10.17660/actahortic.2018.1202.15
|View full text |Cite
|
Sign up to set email alerts
|

Phenotyping of Brassica napus L. plantlets affected during in vitro growth by the presence of epoxiconazole

Abstract: Epoxiconazole like others triazole fungicides are known to be persistent in the soil. Several studies using foliar application experiments demonstrated the effect of its triazole metabolite as plant growth regulator through the anti-gibberellin activity. And notably, the reduction of Brassica napus L. growth can be attributed to the inhibition of gibberellin biosynthesis at the stage of conversion of ent-kaurene to entkaurenoic acid. We describe here an in vitro experiment studying the relationship between epo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
2
0
1
Order By: Relevance
“…IGS is a sulfur-containing secondary metabolite, whose biosynthesis requires GSH as a sulfur donor. It has been frequently reported that the biosynthesis of IGS was responsive to Cd stress ( Jakovljević et al, 2013 ; Durenne et al, 2017 ), although the physiological significance of this response is not clear. Our study found that Trp inhibited Cd-induced IGS biosynthesis.…”
Section: Discussionmentioning
confidence: 99%
“…IGS is a sulfur-containing secondary metabolite, whose biosynthesis requires GSH as a sulfur donor. It has been frequently reported that the biosynthesis of IGS was responsive to Cd stress ( Jakovljević et al, 2013 ; Durenne et al, 2017 ), although the physiological significance of this response is not clear. Our study found that Trp inhibited Cd-induced IGS biosynthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Organic manure and biofertilizers improve soil health and crop quality, as evidenced by a study on red cabbage cultivation assessing nutrient efficiency, productivity, and soil sustainability [ 15 ]. In addition, a field experiment was conducted to evaluate the growth, productivity, and economics of cabbage in the grid zone as influenced by different levels of zinc and sulfur reported that growth parameters such as plant height, plant spread, number of leaves per plant at all crop growth stages, yield attributing characters, length and diameter of head and weight per head, cabbage yield per hectare net return, and benefit cost ratio increased with increasing levels of sulfur from 20 to 80 kg/ha and zinc from 2 to 8 kg/ha and the crop responded only up to 60 kg S/ ha and 6 kg Zn/ha [ 61 , 62 ]. During a 2017 experiment in Ghana's Kintampo North Municipality, evaluating cabbage response to various soil amendments from August to November, poultry manure matched NPK (15-15-15) and outperformed other treatments across all measured parameters, while cow dung and goat manure also exhibited promising results [ 63 , 64 ].…”
Section: The Effect Of Nitrogen On the Cabbage Yieldmentioning
confidence: 99%
“…Epoksikonazol adalah fungisida triazole yang berspektrum luas. Epoxiconazole mampu mengganggu sintesis membran sel jamur sebagai penghambat biosintesis ergosterol serta Bahan aktif pyraclostrobin mampu mengurangi infeksi endofit dibandingkan dengan kontrol (Durenne et al, 2018). Bahan aktif difenokonazol mampu menurunkan frekuensi Fusarium.…”
Section: Identifikasi Keanekaragaman Jamur Endofitunclassified